(untitled) (JURNAL KEPERAWATAN, 2015)
Abstract: Hospitalization cause the child has traumatic and raises the symptoms such as regression response, worried about the separation, apathy, fear, and sleep disorders. The negative impact is related to the length ang large amount of the patients, various of the invasive procedures, and parental anxiety. Any action taken in solving the children problem must be based on the atraumatic care principles or therapeutic care. The objective of this research is to know the effect of atraumatic care application to the child’s anxiety response of the hospitalization. The research design is quasy-experimental design using pretest-posttest with control group. There are 34 childrens, 1-14 years old that become the samples of this research. The research uses non-probability sampling with consecutive sampling method used infusion consists of 17 intervention group with ice cube compress and giving toys and 17 childrens in control group without intervention. The results is the research is taken using paired t-test and unpaired t-test in intervention group (p = 0,000). The conclusion shows the existence of atraumatic care effect to the child’s anxiety response of the hospitalization. This research suggestions is the use of ice cube compress and giving toys during the infusion installation can decrease the children anxiety. Keywords : Atraumatic care, child, anxiety, hospitalization Abstrak: Hospitalisasi menyebabkan anak mengalami trauma dan menimbulkan gejala berupa respon regresi, cemas terhadap perpisahan, apatis, ketakutan, dan gangguan tidur. Dampak negatif ini berkaitan dengan lamanya dan banyaknya jumlah pasien, berbagai prosedur invasif, serta kecemasan orangtua. Tindakan yang dilakukan dalam mengatasi masalah anak apapun bentuknya harus berlandaskan pada prinsip atraumatic care atau asuhan yang terapeutik. Tujuan penelitian ini untuk mengetahui pengaruh penerapan atraumatic care terhadap respon kecemasan anak yang mengalami hospitalisasi. Desain penelitian yang digunakan adalah quasy-experimental design dengan rancangan penelitian pretest-posttest with control group. Sebanyak 34 anak berusia 1-14 tahun menjadi sampel penelitian menggunakan pendekatan sampling non probabilitas dengan metode consecutive sampling yang dilakukan pemasangan infus yang terdiri dari 17 anak kelompok intervensi kompres es batu dan pemberian mainan dan 17 anak kelompok kontrol atau tanpa intervensi. Hasil penelitian menggunakan uji t berpasangan dan uji t tidak berpasangan didapatkan pada kelompok intervensi (p= 0,000). Kesimpulan menunjukkan adanya pengaruh penerapan atraumatic care terhadap respon kecemasan anak yang mengalami hospitalisasi. Saran penelitian ini yaitu kompres es batu dan pemberian mainan pada saat pemasangan infus dapat menurunkan kecemasan pada anak. Kata kunci : Atraumatic care, anak, kecemasan, hospitalisasi